2013
DOI: 10.1186/1471-2458-13-699
|View full text |Cite
|
Sign up to set email alerts
|

Screening and brief interventions for hazardous and harmful alcohol use among patients with active tuberculosis attending primary public care clinics in South Africa: results from a cluster randomized controlled trial

Abstract: BackgroundIn 2008 the World Health Organization (WHO) reported that South Africa had the highest tuberculosis (TB) incidence in the world. This high incidence rate is linked to a number of factors, including HIV co-infection and alcohol use disorders. The diagnosis and treatment package for TB and HIV co-infection is relatively well established in South Africa. However, because alcohol use disorders may present more insidiously, making it difficult to diagnose, those patients with active TB and misusing alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 38 publications
1
103
0
6
Order By: Relevance
“…Despite the high prevalence of heavy alcohol use in SSA and in Uganda, interventions to reduce alcohol use are not widespread in this region, particularly outside large urban areas, underscoring a major public health gap (Hahn et al, 2011). Although provision of health education materials and cognitive behavioral therapy may be promising in reducing alcohol consumption among HIV-infected individuals in some settings, scale-up of these programs remain limited (Papas et al, 2011; Peltzer et al, 2013; Pengpid et al, 2013a). Moreover, problem alcohol use is believed to often go undetected in this region; one study in primary care settings found that only 7% of drinkers have been asked about their alcohol consumption by their medical providers (Kullgren et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high prevalence of heavy alcohol use in SSA and in Uganda, interventions to reduce alcohol use are not widespread in this region, particularly outside large urban areas, underscoring a major public health gap (Hahn et al, 2011). Although provision of health education materials and cognitive behavioral therapy may be promising in reducing alcohol consumption among HIV-infected individuals in some settings, scale-up of these programs remain limited (Papas et al, 2011; Peltzer et al, 2013; Pengpid et al, 2013a). Moreover, problem alcohol use is believed to often go undetected in this region; one study in primary care settings found that only 7% of drinkers have been asked about their alcohol consumption by their medical providers (Kullgren et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a cluster randomised controlled trial adopted in 14 TB clinics in South Africa and aimed at reducing problem drinking, no difference was found between the Information-Motivation-Behavioural Skill group and the control group (Peltzer et al, 2013). Our study participants were a vulnerable group of low socio-economic status, dealing with several co-morbidities (tobacco smoking, tuberculosis, being HIV-positive, and in some cases also illicit drug use).…”
Section: Discussionmentioning
confidence: 86%
“…However, few studies have examined the efficacy of SBIRT in South Africa. These demonstration projects were part of a WHO strategy to address alcohol problems in developing countries and were conducted in health care settings that included hospital outpatients (17, 18) and rural settings (19). These studies demonstrated that nurses and community health workers were strategic implementation agents in health care settings (17).…”
Section: Introductionmentioning
confidence: 99%
“…These demonstration projects were part of a WHO strategy to address alcohol problems in developing countries and were conducted in health care settings that included hospital outpatients (17, 18) and rural settings (19). These studies demonstrated that nurses and community health workers were strategic implementation agents in health care settings (17). There are good evidence and compelling logic to support the allocation of tasks in health-system delivery to the least costly health worker capable of doing that task reliably (20).…”
Section: Introductionmentioning
confidence: 99%